12, 22, 33, 34, 44, 44
Mean:
Median:
Mode:
Range:​

Answers

Answer 1
Answer:

Answer:Mean (Average) 31.5

Median 33.5

Range 32

Mode 44, appeared 2 times

Step-by-step explanation:


Related Questions

You need 2 eggs for a muffin recipe that makes 12 muffins. If you want to make 36 muffins, what should you do?
How to graph y=3x-8​
4 people divide 10 scoops of lentils equally.About how many scoops of lentils does each person get?
heather allen works for the public works department as an electrical inspector. she earns $17.60 per hour for a 36 hour week. Her overtime rate is 1.5 times her regular hourly rate. this week she worked her regular 36 hours plus 8 hours of overtime. what is her total pay?
David wants to buy 3 avacados and some apples. The price of 1 avocado is $1.50. The prices of apples is $1.00 per pound. David can spend less than $15. Write an inequality that represents the avacado and the number of pounds of apples (a) David can buy.

What is the solution to the system?-2x + y + 6z = 1
3x + 2y + 5z = 16
7x + 3y – 4z = 11

Answers

Answer:

x = 4, y = -2, z = 3

Step-by-step explanation:

\left\{\begin{array}{ccc}-2x+y+6z=1&(1)\n3x+2y+5z=16&(2)\n7x+3y-4z=11&(3)\end{array}\right\n\n(1)\n-2x+y+6z=1\qquad\text{add}\ 2x\ \text{to both sides}\ny+6z=2x+1\qquad\text{subtract}\ 6z\ \text{from both sides}\ny=2x-6z+1\n\n\text{Substitute it to (2) and (3):}\n\n\left\{\begin{array}{ccc}3x+2(2x-6z+1)+5z=16\n7x+3(2x-6z+1)-4z=11\end{array}\right\qquad\text{use the distributive property}\n\n

\left\{\begin{array}{ccc}3x+4x-12z+2+5z=16&\text{subtract 2 from both sides}\n7x+6x-18z+3-4z=11&\text{subtract 3 from both sides}\end{array}\right\n\left\{\begin{array}{ccc}7x-7z=14&\text{divide both sides by 7}\n13x-22z=8\end{array}\right\n\left\{\begin{array}{ccc}x-z=2&\text{multiply both sides by (-13)}\n13x-22z=8\end{array}\right

\underline{+\left\{\begin{array}{ccc}-13x+13z=-26\n13x-22z=8\end{array}\right}\qquad\text{add both sides of the equations}\n.\qquad\qquad-9z=-18\qquad\text{divide both sides by (-2)}\n.\qquad\qquad \boxed{z=2}\n\n\text{Put it ot the equation}\ x-z=2:\nx-2=2\qquad\text{add 2 to both sides}\n\boxed{x=4}\n\n\text{Put the values of}\ x\ \text{and}\ z\ \text{to the equation}\ y=2x-6z+1:\n\ny=2(4)-6(2)+1\ny=8-12+1\n\boxed{y=-3}

Which equation could be used to solve the problem? Tony is on a train that travels 99 mi in 1 h.

At that rate, how many miles (d) will the train travel in 9 h ?

A.
d = 99 + 9

B.
d = 99 ÷ 9

C.
d = 9 ÷ 99

D.
d = 99 • 9

Answers

it is D you will have to Multiply because its say How many mile so thats how i find out
The equation is D. If the train goes 99 miles per 1 hour thats 99 multiplied by 1. But if you substitue the 9 in for the 1 then its 99 times 9:)

How do I solve this complex multi-step equation 2x + (-2 )= 10x - 4 ?

Answers

All you have to remember is this. Reverse the operation. For example on this problem there is a -2 right? So reverse the operation and (REMEMBER:Always do what you did on one side to the other side) then you would have +2 on both sides. You do the same for variables and all of the numbers and result with 8x=2, so divide by 8 and get x=1/4
2x-2=10x-4
-8x=-2
x=1/4

What is bigger, 4,000,000 mm or 4km

Answers

4,000,000 mm is equal to 4 km

4,000,000 mm = 4 km
We need to have the same unit to compare.

We can change km to mm

1 km is 1,000,000 mm so,
4 km is 4,000,000 mm

4,000,000 mm = 4,000,000 mm
Both are equal

Does any one know the answer i just got started in this stuff: Write an equation in sloper-intercept form for the following line:y-intercept 3 and slope 3?

Answers

Slope intercept form:
Y= mx +b 
m is the slope
b is the y-intercept
in this case, just plug the numbers into the equation

Answer is Y= 3x + 3

Let me know the answer plz

Answers

Answer:

J. -(1)/(36), (1)/(216), -(1)/(1296)

Step-by-step explanation:

We are given the following geometric sequence and we are to find its 8th term:

-36, 6, -1, (1)/(6),...

Here a_1=-36 and common ratio (r) = (-1)/(6)=(-1)/(6).

The formula we will use to find the next three terms is:

nth term = a_1 * r^((n-1))

5th term = -36 * (-1)/(6)^((5-1))  = -(1)/(36)

6th term = -36 * (-1)/(6)^((6-1))  = (1)/(216)

7th term = -36 * (-1)/(6)^((7-1))  = -(1)/(1296)

Answer:

J

Step-by-step explanation:

Find the common ratio r of the geometric sequence then multiply a term by r to obtain the next term

r = (a_(2) )/(a_(1) ) = (6)/(-36) = - (1)/(6)

The next 3 terms are

(1)/(6) × - (1)/(6) = - (1)/(36)

- (1)/(36) × - (1)/(6) = (1)/(216)

(1)/(216) × - (1)/(6) = - (1)/(1296)